Dorsolateral inner preputial graft urethroplasty for anterior urethral strictures: long-term outcomes from a single tertiary care centre - Tyagi, Shantanu (World J Urol, 2021)
PURPOSE: Buccal mucosa graft (BMG) is long used as favoured substitute by most reconstructive surgeons for substitution urethroplasty (SU). Though inner preputial skin graft (IPG) was described even earlier than BMG, its usage lately has fallen out of favour. The aim of the study was to evaluate the outcome of a SU with IPG from a tertiary care centre. METHODS: A retrospective analysis of prospectively maintained clinical data was conducted at our tertiary care centre enrolling 80 patients with anterior urethral stricture from January 2015 to January 2018. Patients were evaluated for the aetiology, length and site of the urethral stricture. All patients underwent dorsolateral SU with IPG. Post-operative assessment including uroflowmetry and sexual outcomes using IIEF and MSHQ-EJD questionnaires was done at 3 weeks, 3 months, 12 months and half-yearly thereafter. Success was defined by the stable maximum urinary flow value > 14 ml/s or urethral calibration with 16 French Foley catheter. RESULTS: Mean age of patients was 40 years (18–69). The most common aetiology was post-instrumentation (65%) and 60% had stricture at penobulbar site. Mean stricture length was 65 mm. At a mean follow-up of 48 months (range 30–66 months), successful outcomes were seen in 69/80 (87%). Patients with failure were managed with optical internal urethrotomy (OIU). Uroflowmetry and obstructive symptoms significantly improved and sexual function remained unaffected using IPG for SU. CONCLUSIONS: Preputial graft is a tissue familiar to the urologist, located very close to the surgical field, easily harvested and operated under regional anaesthesia. Overall success outcomes are acceptable to BMG urethroplasty. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00345-021-03613-9.